Antimicrobial Resistance Patterns in Women with Positive Urine Culture: Does Menopausal Status Make a Significant Difference?. (13th April 2017) - Miotla, Pawel; Romanek-Piva, Katarzyna; Bogusiewicz, Michal; Markut-Miotla, Ewa; Adamiak, Aneta; Wróbel, Andrzej; Zebrowska, Małgorzata; Wawrysiuk, Sara; Mendyk, Katarzyna; Rechberger, Ewa; Jakubczak, Agata; Rechberger, Tomasz
Abstract : Aim . Urinary tract infection (UTI) is considered one of the most common bacterial infections in women. The aim of this study was to investigate the types of uropathogens present, as well as the degree of antimicrobial drug resistance seen among premenopausal ( n = 2748 ) and postmenopausal ( n = 1705 ) women with uncomplicated UTI. Methods . Urinary samples ( n = 4453 ) collected from women with UTI were analyzed in terms of uropathogens present. These were considered as positive if bacterial growth was ≥10 5 colony forming units (CFUs)/mL. Susceptibility and resistance testing for commonly used antibiotics was subsequently assessed. Results . The most common uropathogens cultured from urine samples were Escherichia coli (65.5%), followed by Enterococcus faecalis (12.2%), Klebsiella pneumoniae (4.7%), and Proteus mirabilis (4.2%). The resistance to ampicillin exceeded 40%, independently of menopausal status. Of note, resistance to ciprofloxacin exceeded 25% among postmenopausal patients. Moreover, resistance of all uropathogens to commonly used antimicrobials was significantly higher in postmenopausal women. Conclusion . Due to the high resistance rate, ampicillin, ciprofloxacin, and the trimethoprim/sulfamethoxazole combination should be avoided in treating postmenopausal women affected by UTI without being indicated by initial urine culture report. Finally, cephalexin and cefuroxime are promising alternatives as initial treatment in postmenopausal women.